Fast Determination of Lithium Content in Spent Cathodes for Direct Battery Recycling. (25th May 2020) - Li, Xuemin; Dogan, Fulya; Lu, Yingqi; Antunes, Christopher; Shi, Ying; Burrell, Anthony; Ban, Chunmei
Abstract: Determination of the lithium ion content in cathode materials, which is currently performed by inductively coupled plasma mass spectrometry (ICP−MS), involves tedious procedures and error‐prone preparation. This work introduces a new methodology to quickly determine the lithium content in spent cathode materials (LiNi x Mn y Co z O2, x + y + z = 1, NMC) using a thermalgravimetric analysis, which bypasses the use of ICP−MS and significantly reduces the cost and time required for determining the lithium content. Based on this new method, a new approach is developed to identify spent cathode materials suitable for direct relithiation recycling. Finally, these new methods have been applied to investigate the effectiveness of direct electrochemical−relithiation on recycling the spent cathodes, and provide insights for future development of direct battery materials recycling. Abstract : Sorting and developing appropriate strategies for the end‐of‐life (EoL) batteries is beneficial to the battery recycling industry. Understanding the major degradation behavior of the spent cathodes is necessary for battery sorting. A methodology based on the thermal gravimetric properties of the materials is demonstrated for sorting EoL batteries that can be directly recycled by relithiation.